Advancing methodological thought and practice - Russell Crook, T. Russell; Lê, Jane K.; Smith, Anne D. (Research methodology in strategy and management ;, 2020)
Research Methodology in Strategy and Management advances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed. This volume explores cutting-edge methodological approaches to the study of organizations, managers, and strategy, and offers 'how to' guides for applying these approaches. It also includes retrospective accounts by Joe Hair and John van Maanen, of the key methodological contributions they have made throughout their careers. This is an informative book for all academics and researchers working in the fields of management, strategy, international business, entrepreneurship and organization theory.